IMPLEMENTATION OF THE ARTIFICIAL IMMUNE SYSTEM ALGORITHM FOR SECURITY INFORMATION AND EVENT MANAGEMENT SYSTEMS - Çelik, Y.; Fındık, O.; Alaca , Y.; Assanova, B.; Sharmukhanbet , S. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
One of the most used technologies in computer and network security is Security Information and Event Management (SIEM) systems. A SIEM system is a tool that collects logs of all software and hardware connected to the network, detects security violations using these logs, and generates alarm notifications. The SIEM system generates several alerts during operation. It is an essential problem because of the abundance and the correctness of these alerts generated. In this paper, we implement the Artificial Immune System (AIS) algorithm to generate more stable alerts and to increase the verification rates of the alerts produced by SIEM systems. The results show that the adaptation of the AIS algorithm to SIEM systems is successful. When we apply the SIEM systems powered by AIS, then we had got more successful result than the traditional SIEM systems.